2013
DOI: 10.1063/1.4816620
|View full text |Cite
|
Sign up to set email alerts
|

Competition between CoOx and CoPt phases in Pt/Co/AlOx semi tunnel junctions

Abstract: 10 pagesInternational audienceWe report on the evolution of the structure and composition of a Pt(3 nm)/Co(0.6 nm)/AlOx(2 nm) trilayer sputtered on Si/SiO2 under oxidation and annealing processes by combined x-ray reflectivity and x-ray absorption studies. We describe the progressive and inhomogeneous oxidation of the layers by increasing the oxidation time. Before annealing, the layers have lower density than bulk samples and noticeable roughness. After thermal annealing, a significant improvement of the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…The CoO thin layer spectrum was obtained from a Pt-Co and CoO-AlO x multilayer substrate reported in Ref. [48]. Additional Co bonding environments such as Pt-Co and Co-Al in the absorption signal of the CoO thin layer spectrum, which are not present in our samples, may explain the lower quality of fits compared to the CoO bulk spectrum.…”
Section: B Edge Energy Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…The CoO thin layer spectrum was obtained from a Pt-Co and CoO-AlO x multilayer substrate reported in Ref. [48]. Additional Co bonding environments such as Pt-Co and Co-Al in the absorption signal of the CoO thin layer spectrum, which are not present in our samples, may explain the lower quality of fits compared to the CoO bulk spectrum.…”
Section: B Edge Energy Analysismentioning
confidence: 94%
“…We tested different reference spectra, including bulk Co metal, the unholed Co substrate, CoO bulk, CoO thin film (1.5 nm thickness from Ref. [48]), as well as Co 3 O 4 bulk. The two standard compounds that fit best the sample spectrum were evaluated from the χ 2 parameter, which is an indicator for the quality of the fit.…”
Section: B Edge Energy Analysismentioning
confidence: 99%
“…Underoxidized (shorter oxidation time) or overoxidized (longer oxidation time) interfaces exhibit weaker interfacial PMA (IPMA) at room temperature. It is also found that, upon annealing, oxygen tends to migrate to the Co=AlO x interface, thereby maximizing the interfacial PMA [15,16]. From an application point of view, this IPMA is very interesting in the context of STT MRAM since it allows obtaining out-of-plane magnetized magnetic tunnel junction with weak Gilbert damping and, therefore, low write current [12].…”
Section: Introductionmentioning
confidence: 91%
“…In this paper, low-temperature characterization of the anisotropy in Pt=Co=AlO x trilayers is performed and discussed in light of the previously investigated structural and chemical properties of these systems [16]. The samples of this study are the same as the ones measured in the previous studies [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation